Affectivity and the nature of the sage: Gleanings from a Tang Daoist master - CHAN, Alan Kam Leung (Institutional Knowledge at Singapore Management University, 2010)
This essay explores the place of qing in conceptions of the nature and being of the sage, focusing on the Tang Daoist master Wu Yun. What it seeks to show is that assumptions about the attainability of “sagehood” and the “nature” (xing) of human beings inform the interpretation of qing. In this context, the idea that the sage is quintessentially wuqing, marked by the absence of desire and emotions, will be examined. I will close with a comparative note on a Confucian account of the same period—namely, the Fuxing shu by Li Ao.